Mindfullness Based Intervention dalam Upaya Meningkatkan Regulasi Kematangan Emosional Remaja - Tastiara Tastiara; Berlian Cahyani; Nadia Nadia; Rizki Novirson; Resti Okta Sari (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the effectiveness of Mindfulness Based Intervention (MBI) in enhancing emotional regulation in adolescents through a Systematic Literature Review (SLR) approach. The research method was conducted by reviewing and analyzing 17 articles or journals published between 2018 and 2025 that are relevant to the topic discussed. The results of the study show that MBI has been consistently proven effective in increasing emotional awareness, self-acceptance, and the use of adaptive emotion regulation strategies in adolescents. The implementation of MBI is positively correlated with decreased levels of stress, anxiety, depression, aggressive behavior, as well as increased resilience and concentration. These findings indicate that MBI has significant potential to be integrated into Guidance and Counseling programs in schools. This research contributes by providing a strong scientific foundation regarding the effectiveness of MBI on adolescent emotion regulation, as well as offering evidence-based intervention alternatives for school counselors to support students' emotional development and psychological well-being.